Rapid solidification structure and grain refinement mechanism of undercooled Cu60Ni40 alloys. Issue 2 (22nd January 2022) - Wang, Hongfu; Tang, Cheng; An, Hongen; Xu, Xiaolong; Zhao, Yuhong
Abstract : Applying the composite technology of molten glass coating and superheating method, the molten Cu60 Ni40 alloy has obtained different undercooling degrees. The microstructure of the alloy during rapid solidification was observed by metallographic microscope, and the evolution process of microstructure morphology was systematically studied. It is found that two significantly different grain refinement phenomena occur in the range of low undercooling and high undercooling. The characteristics of high proportion of large angle grain boundaries, random grain orientation and a large quantity of twin boundaries show that the grain refinement structure under high undercooling is due to recrystallisation. And the microhardness test results show that the average hardness of the grain refinement structure under large undercooling suddenly decreases sharply at the critical undercooling, which also confirms the recrystallisation mechanism of the refined grain under high undercooling.